Educational Management of Inclusive Support Systems for Adolescents with Intellectual Disabilities: Implication for Early Diagnosis and Intervention Fidelity - Ebaye, Asenath; Igu, Ntasiobi C.N.; Elechi, Catherine Nkiruka; Ukwuaba, Loretta Chika; Eze, Thecla Amoge; Onoyima, Ngozi Stephenia; Agada, Chinyelugo Fidelia; Kelechi, Onubuleze Franklin; Ngozi, Odenigbo Veronica; Patricia, Aka Chinelo; Undie, Peter; Ofem, Usani Joseph (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
This research investigated how educational management influences early identification and the consistent implementation of inclusive interventions for adolescents with intellectual disabilities (IDs) in Nigerian secondary schools. Employing a descriptive research design, the study sampled 377 participants, including school administrators, special educators, and classroom teachers from both public and private schools in Cross River State, using a stratified sampling approach. Data were gathered via a structured questionnaire and analyzed through descriptive statistical methods. The results indicated that educational management effectively facilitates early diagnosis by providing timely screening, allocating necessary resources, organizing staff training, promoting collaborative practices, communicating policies clearly, and systematically monitoring identification data. In contrast, the study revealed that the fidelity of intervention implementation was generally low. Key inclusive strategies, such as individualized education plans, differentiated instruction, functional life-skills training, assistive technology utilization, and classroom modifications, were applied inconsistently. Moreover, managerial practices were found to have limited impact on intervention fidelity, reflecting insufficient supervision, guidance, resource allocation, and feedback processes. These findings highlight a gap between inclusive education policy and its execution at the classroom level. The study emphasizes the need for strengthened professional development, enhanced monitoring, systematic supervision, and collaborative structures to improve the consistency of interventions and promote positive developmental outcomes for adolescents with intellectual disabilities.